Druga celovita jezikovnopolitična raziskava o potrebah jezikovnih uporabnikov v RS in uporabnikov slovenščine v sosednjih državah in po svetu - Ahačič, Kozma (Slavistična revija, 2025)
The article presents an overview of methodological premises of the work carried out within the target research project The Second Comprehensive Language Policy Survey on the Needs of Language Users in Slovenia and Users of Slovenian in Neighbouring Countries and Worldwide. The aim of the project was to provide a comprehensive language policy overview of the various domains relevant to Slovenian language policy. The focus is on the presentation of an online survey through which the linguistic needs, practices, and attitudes of language users in the Republic of Slovenia were analysed holistically. The profile of respondents is presented in greater detail, and the article also offers several key findings of the study in the language policy domains that are highlighted.
Keywords: jezikovna politika; jezikovna raba; jezikovni status; jezikovni uporabnik; language policy; language status; language use; language user; methodology; metodologija; online survey; Slovenian language; slovenščina; sociolinguistics; sociolingvistika; spletna anketa